Self-Efficacy dan Hubungannya Terhadap Karakteristik Siswa SMP pada Pembelajaran Matematika - Pingki Neng Avipah (Universitas Cokroaminoto Palopo, 2023)
Learning mathematics at school is still considered scary, difficult to understand, and too many formulas. Students are not sure and confident when learning mathematics. So this study aims to increase self-efficacy and student characteristics so that students are more enthusiastic about learning mathematics. The method used in this research is a survey method with a quantitative approach. Data collection used a Likert scale. The data collected was tested for validity and reliability tests using the SPSS statistical 24 application. The results of the correlation test in this study were 0.559 with a significance of 0.000. With a positive variable, the result is that the higher the characteristic, the higher the self-efficacy.